CSR in an Investment Facilitation Framework for Development: From a "race to the bottom" to a "march to the top" - Rafael Ramos Codeço; Ana Rachel Freitas da Silva (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
The apparent trade-off between improving responsible business conducts and preserving international competitiveness has led some developing countries to join the so-called ''race to the bottom''. The Investment Facilitation Framework for Development can help developing countries overcome this harmful competition and address the issue in a progressive and cooperative way.
Keywords: 330